Explorando a matemática do jogo torre de hanói - Silva, Renato José Menezes (Universidade Federal Rural do Semi-Árido, 2018)
In this work we present the Tower of Hanoi game, we explore its historical aspect and also its mathematical potential. We started by developing a good strategy to sell the Tower respecting is rules, this strategy will serve as a basis for future demonstrations. Through observations we notice some patterns about the minimum number of movements to win the game and each piece, we formulate a theory and in sequence are present some demonstrations. Going deeper, we notice a close relationship between some demonstrations. Going deeper, we notice a close relationship between the game and the binary number system, which gives us incredible results, such as determining which exact piece should be moved in a certain movement without having to perform the previous ones. Another application of binary numbers is to determine the exact position of each part in a certain movement
Keywords: Jogos; Ensino de matemática; Torre de hanói; Game; Mathematics teaching; Tower of hanoi; CIENCIAS EXATAS E DA TERRA::MATEMATICA